New tools to prevent cancer growth and spread: a 'Clever' approach - Maija Hollmén; Carlos R. Figueiredo; Sirpa Jalkanen (NATURE PUBLISHING GROUP, 2022)
Clever-1 (also known as Stabilin-1 and FEEL-1) is a scavenger receptor expressed on lymphatic endothelial cells, sinusoidal endothelial cells and immunosuppressive monocytes and macrophages. Its role in cancer growth and spread first became evident inStab1(-/-)knockout mice, which have smaller primary tumours and metastases. Subsequent studies in mice and humans have shown that immunotherapeutic blockade of Clever-1 can activate T-cell responses, and that this response is mainly mediated by a phenotypic change in macrophages and monocytes from immunosuppressive to pro-inflammatory following Clever-1 inhibition. Analyses of human cancer cohorts have revealed marked associations between the number of Clever-1-positive macrophages and patient outcome. As hardly any reports to date have addressed the role of Clever-1 in immunotherapy resistance and T-cell dysfunction, we performed data mining using several published cancer cohorts, and observed a remarkable correlation between Clever-1 positivity and resistance to immune checkpoint therapies. This result provides impetus and potential for the ongoing clinical trial targeting Clever-1 in solid tumours, which has so far shown a shift towards immune activation when a particular epitope of Clever-1 is blocked.